Definition of Rainfall Intensity (R-Factor) When Soil Erosion by Interpolation (Journal of Geography and Environmental Management, 2019)
Since the process of soil erosion is one of the intensive trends that have a significant negative impacton land resources, as well as the national economy, now the necessary work to determine the prioritytypes of erosion processes, the calculation of the process of soil erosion, its optimization and organizationof preventive measures. One of the main factors affecting soil erosion is rainfall (R). Since its volumeand intensity of the fall leads to the emergence of erosion in the soil. In this paper, the intensity of precipitation(R-factor) is calculated by interpolation in GIS technology and an algorithm for determining theR-factor is proposed. Chizha-1 river extends from North to South to 72 km, from West to East in 33 km.In this regard, the precipitation occurs from South to North. With precipitation of 300 mm per year, 16%of the southern massifs to the North change their value. Soil erosion is more common in fine-grainedsoils, in areas with high rainfall and strong winds. When severe soil erosion, reduced soil fertility, damagesown seeds, the deteriorating quality of rangeland agriculture. All this causes huge damage to agriculture.In this regard, this work focuses on this topic and the study found that the annual amount of precipitationentering the agricultural lands of the Chizha-1 river basin varies from 300mm to 325mm.